Gamifikasi Berbasis Poin dalam Pembelajaran Matematika Sekolah Dasar - Makhfirah Jannatun Jannah; Tania Valensya Br Sihombing; Indah Saputri Pandiangan; Annekarela; Jesse Clairine Buulolo; Elvi Mailani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Mathematics learning in elementary schools still faces the problem of low student participation and motivation during the learning process, which results in less than optimal student engagement in understanding mathematical concepts. This study aims to analyze the implementation of a point system in mathematics learning and its impact on student learning outcomes, motivation, and participation. The study used a mixed methods approach with an embedded design. The subjects consisted of 28 second-grade students of Baghdad Madani Integrated Islamic Private Elementary School and a class teacher. Quantitative data were obtained through documentation of mathematics report card scores and student point acquisition records, while qualitative data were collected through semi-structured interviews with teachers. Quantitative data analysis was conducted using descriptive statistics in the form of average scores and percentage of learning completion, while qualitative data were analyzed through data reduction, data presentation, and drawing conclusions. The results showed that all students achieved learning completion with an average mathematics score of 85.04. In addition, the implementation of a point system was proven to increase student learning motivation, activeness, courage to answer questions, and discipline during learning. These findings indicate that a point system can be a simple and effective strategy to increase student engagement while supporting the achievement of mathematics learning outcomes in elementary schools.